Biographical Criticism Significance in Dante Alighieri’s Inferno for Literary Research Subject - Putri, Silvia Eka; Permanasari, Pradnya (JELLE, 2024)
Biographical criticism is easier to do to literary works that reflect the author’s biography. This research used qualitative research. In this research, interview and Inferno were the data sources. Three lecturers of Pekalongan University are the interviewees of this research. The objective of this research is to find out the significance of biographical criticism analysis for Literary Research subject of Pekalongan University. The result showed that this research can enrich students understanding about biographical criticism. This research also can be an example or reference to introduce biographical criticism to students. However, the novel is quite old to be an example. Instead of using novel which written long time ago, the writer can choose latest novel which more related to the students. The presentation of the findings needs to be shortened to show a compacted and concise form to save students’ time in reading this.